Thermodynamic and economic analysis of a trigeneration system based on liquid air energy storage under different operating modes. (1st October 2020) - Gao, Zhaozhao; Guo, Luna; Ji, Wei; Xu, Hao; An, Baolin; Wang, Junjie
Highlights: A variable trigeneration system based on liquid air energy storage is proposed. Systematic thermo-economic analysis for different seasons and regions is made. Better performance comes from higher ambient temperature and energy price. Abstract: Liquid air energy storage is a promising long-time energy storage technology with the advantages of large capacity and no geographical restrictions. However, the cycle efficiency still has potential to improve and the operation modes need to be investigated. Thus a novel trigeneration system based on the liquid air energy storage is proposed. The system can store the off-peak electricity and supply the cooling, heating and power at the peak time. With different needs for the multiple energy, the optimal configuration of the trigeneration system for different seasons is studied, and the thermodynamics and economics are both analyzed. The results show that the round-trip efficiencies of the system in winter, the transition season and summer for Jinan City are 55.41%, 55.35% and 54.68%, respectively. The dynamic payback period and the levelized cost of energy for the trigeneration system are 5.46 years and 0.13 /kWh, respectively. Furthermore, the thermo-economic analysis of five typical regions in China is carried out. Guangzhou City owns the best economic performance with the largest annual total profit of 709.81 k and the smallest dynamic payback period of 4.49 years. It can be concluded that the system has inspiring adaptability and feasibility under variable operation modes.